2021
DOI: 10.11613/bm.2021.020707
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of the three assays for determination of fecal calprotectin in inflammatory bowel disease

Abstract: Introduction Fecal calprotectin is a biomarker for monitoring inflammatory bowel disease (IBD) activity. Our aim, therefore, was to evaluate two new assays, the point of care test Quantum Blue and the Liaison Calprotectin with respect to the Calprest, commonly used assay, and to determine their performance for IBD diagnosis. Materials and methods We included 73 prospective patients with IBD. Fecal calprotectin was measured and analysed with the routine Calprest assay an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…This study also showed that the combination of serum calprotectin with CRP or albumin may be helpful in predicting treatment escalation, especially in patients with CD. In patients with IBD who are in clinical remission, the measurement of the FC concentration can be used as a biological marker for the presence of inflammation of the mucous membrane [ 64 , 65 ]. The fecal calprotectin concentration reflects the degree of the pathological neutrophilic infiltration of the intestinal wall.…”
Section: Consequences Of the Use Of Antibiotics On Diseases Of Neonat...mentioning
confidence: 99%
“…This study also showed that the combination of serum calprotectin with CRP or albumin may be helpful in predicting treatment escalation, especially in patients with CD. In patients with IBD who are in clinical remission, the measurement of the FC concentration can be used as a biological marker for the presence of inflammation of the mucous membrane [ 64 , 65 ]. The fecal calprotectin concentration reflects the degree of the pathological neutrophilic infiltration of the intestinal wall.…”
Section: Consequences Of the Use Of Antibiotics On Diseases Of Neonat...mentioning
confidence: 99%